Potential benefits and challenges on the use of phytochemicals for obese COVID-19 patients: A review - Murtala Bello Abubakar; Abdurrahman Pharmacy Yusuf; Dawoud Usman; Ibrahim Babangida Abubakar; Babangida Sanusi Katsayal; Idris Zubairu Sadiq; Shehu Muhammad Hassan; Gilead Ebiegberi Forcados; Kasimu Ghandi Ibrahim; Shuaibu Abdullahi Hudu; Aliyu Muhammad (Elsevier, 2024)
Background: COVID-19 produces a great burden on obese individuals. Due to the age-long use of medicinal herbs in the management of obesity, their potential against the COVID-19 pandemic is increasingly investigated. This study aims to review phytochemicals or bioactive compounds with the potential of being useful for obese COVID-19 patients. Methods: Using search terms that include pairwise combinations of either COVID-19 or obesity with each of nine selected phytochemicals (epigallocatechin gallate, rutin, astaxanthin, resveratrol, genistein, curcumin, quercetin, ellagic acid, and hesperidin). Relevant articles published from January 2009 to August 2023 were retrieved from PubMed. Results: A total of 43 papers (17 clinical trials, 12 preclinical studies, 3 systemic reviews of randomized controlled trials, and 11 other review papers) met the inclusion criteria and were discussed in this review. These include research articles reporting the anti-COVID-19 properties of the selected phytochemicals, which have previous or recent "clinical evidence" against overweight or obesity Conclusion: Phenolic compounds make up to eight out of the nine selected bioactive compounds and are, therefore, concluded to be the best class of phytochemicals for managing obese COVID-19 patients.